Flow cytometric method transfer: Recommendations for best practice. Issue 1 (18th November 2020) - Cabanski, Maciej; Oldaker, Teri; Stewart, Jennifer J.; Selliah, Nithianandan; Eck, Steve; Green, Cherie; Litwin, Virginia; Vitaliti, Alessandra
Abstract: As with many aspects of the validation and monitoring of flow cytometric methods, the method transfer processes and acceptance criteria described for other technologies are not fully applicable. This is due to the complexity of the highly configurable instrumentation, the complexity of cellular measurands, the lack of qualified reference materials for most assays, and limited specimen stability. There are multiple reasons for initiating a method transfer, multiple regulatory settings, and multiple context of use. All of these factors influence the specific requirements for the method transfer. This recommendation paper describes the considerations and best practices for the transfer of flow cytometric methods and provides individual case studies as examples. In addition, the manuscript emphasizes the importance of appropriately conducting a method transfer on data reliability.